Twenty-three medication-taking traits and stroke: A comprehensive Mendelian randomization study - Shao, Wenbo; Li, Taozhi; Wang, Yukun; Shan, Shizhe; Zhang, Haiyu; Xue, Yanxing (Frontiers in Cardiovascular Medicine, 2023)
Abstract Background: Certain medication categories may increase the risk of stroke. Nonetheless, the evidence regarding the causal relationship of medication-taking in promoting stroke and subtypes is deficient. Methods: We evaluated the causal effect of a genetic predisposition for certain medication categories on stroke and subtypes (ischemic and hemorrhagic categories) by a two-sample Mendelian randomization analysis. Data for 23 medication categories were gathered from a genome-wide association study (GWAS) involving 318177 patients. The Medical Research Council Integrative Epidemiology Unit Open GWAS database and the FinnGen consortium were used to gather GWAS data for stroke and subtypes. Inverse variance weighted, MR-Egger and weighted median were used for the estimation of causal effects. Cochran’s Q test, MR-Egger intercept test and leave-one-out analysis were used for sensitivity analyses were employed to carry out sensitivity analyses. Results: Ten medication categories were linked to a high stroke risk. Nine categories were linked to a high-risk ischemic stroke. Five categories were associated with small vessel ischemic stroke. Nine categories were positively associated with large artery atherosclerotic ischemic stroke. Three categories causally increased the possibility of cardioembolic ischemic stroke. Four categories were associated with intracerebral hemorrhage. Four categories were associated with non-traumatic intracranial hemorrhage. Three categories were causally associated with subarachnoid hemorrhage (SAH). And four categories were associated with the combination of SAH, unruptured cerebral aneurysm, and aneurysm operations SAH. Conclusions: This study confirms that some medication categories lead to a greater risk of strokes. Meanwhile, it has an implication for stroke screening as well as direct clinical signiﬁcance in the design of conduction of future randomized controlled trials.